The Relationship Between Social Media Marketing and Online Purchase Intention - Poon Hui Theng; Siti Aisyah Salim (Research in Management of Technology and Business, 2024)
The internet and social media have altered traditional business methods with customer interactions, as well as the ways in which businesses and customers trade. It involves two-way interactive social networking, is inexpensive, widespread, and practical for reaching customers including our research scope, generation Y. Although excellent intergenerational communication exists, they are sophisticated and powerful customers who are challenging to persuade, influence, and keep as customers. Because of this, the cohort uses social media extensively and is constantly seeking out new information. For the reason that, the study aims to explore the relationship between social media marketing and online purchase intention among the generation Y in Malaysia. There are three dimensions which are interaction, entertainment, and electronic-Word-Of-Mouth (e-WOM) will be discussed in this study. The study has surveyed 239 respondents which the target respondents of this study are Gen Y, the current age is 29 to 41 which also known as digital natives born between 1982 and 1994. The sample was assembled using an online survey and questionnaire that conformed with the quantitative research methodology. This study used randomly selecting respondents from the population generation Y without any specific criteria or stratification. A SPSS software program will be used to analyze data collected from respondents among generation Y who are familiar with online shopping to achieve the research purpose. In the form of charts and graphs, the results of the data analysis will assist the researcher in answering the study’s objectives. Based on the analysis, all variables showed a significant relationship with Gen Y online purchase intentions. According to Dimension Entertainment, social media marketing has a significant influence on online purchase intention with a correlation coefficient of 0.428.